Analysis on Practical Teaching Reform of Undergraduate Major of Agricultural and Forestry Economic Management. Issue 3 (June 2020) - Jianlan, Su; Qin, Long
Abstract: This paper selected 21 universities and colleges which own the major of agricultural and forestry economic management as samples, analyzed the current situation and the shortages in professional practice teaching systems, proposed that the universities and colleges should scientifically and reasonably design professional practice teaching system, strengthen the training of responsibility consciousness, professional ethics and innovation ability of students, establish a feedback and adjustment mechanism for the practical teaching system of agricultural and forestry economic management, the aim is to meet the needs of agricultural and rural modernization.